Sistem dan Prosedur Pelayanan Izin Usaha Industri Peternakan Di KabupatenBanjarnegara - Nico Setiad; Indriati Amarin (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
The Banjarnegara Regency One Stop Integrated Licensing and Investment Service (DPMPPTSP) is one of the units inthe region that organizes Online Single Submission. However, the implementation has not been maximized, so I wantto know what obstacles occur in the industrial business permit process in Banjarnegara district. The purpose of thisstudy was to identify and analyze the efforts of the One-Stop Integrated Investment and Licensing Service inimplementing the granting of electrical industrial business permits. And knowing the obstacles that occur in theprocess of implementing industrial business permits in Banjarnegara Regency. The method in this research is usingthe normative juridical method. The data in this study were obtained through library research, namely a series ofreading, recording, and citing books as well as using secondary data or information and explanations through datarequests from relevant agencies based on the objectives. study. The results of this study indicate that the livestockindustry business licensing process online through the Online Single Submission there are obstacles faced by theOffice of Investment and One Stop Integrated Services such as incomplete data provided by the applicant in theindustrial business permit process, besides that there are also obstacles to the community such as the type of businessfields in the Online Single Submission that are not yet complete.